(untitled) (Global Journal of Management and Business Research, 2022)
In this paper I review and provide a more extensive theoretical grounding for Porter s five- forces model for the determination of the attractiveness of an industry I argue that the model is incomplete given its implicit assumptions about a firm s financing activities in implementing its competitive strategy It is my opinion that an absolute paradigm for the determination of the attractiveness of an industry must take into consideration the industry s optimal capital structure as well as the tendency for the power of providers of debt capital to vary across industries and to be crucial in the formation of industry profitability